Optimizing Google Drive Media For Writing Paperless Office Letter - Rachmanto, Adi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
University as an institution is equipped with an administration which always includes archiving activities. Making electronic letters can help administrative activities in obtaining cover letters from campus, one of which is a cover letter from the campus to carry out practical work in companies / institutions. Therefore, making manual letters / archives can be equipped with electronic archiving, one of which is the Google Drive application which has the purpose of being a paperless office. The purpose of this study was to create a cover letter making system using the Google Drive application as a support for a paperless office in universities. In the Google Drive application, other applications will also be used, including google form which is used to display the data entry interface, google docs for document creation and google spreadsheet is used for data storage and processing. This research is a descriptive study with a practical and applicable approach. The subjects in this study were secretariat employees and final year students who carried out practical work. The data collection techniques used were observation, interview and documentation. The impact of making this application is to be able to help students to simplify and speed up in obtaining a cover letter for practical work from campus.